2005
DOI: 10.1115/1.2033007
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Journal Bearing Lubrication Effected by Journal Misalignment as a Result of Shaft Deformation Under Load

Abstract: Journal bearing friction pair system is one of the most general and essential parts used in various mechanical devices. A special test bench is developed for the study on lubrication performance of cylindrical journal bearings. The effect of journal misalignment as a result of shaft bending under load is studied. The results show obvious changes at distribution and value of oil film pressure, oil film thickness and oil temperature of journal bearing due to journal misalignment. The higher the load on the shaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The misalignment caused more significant changes in bearing performance when the rotational speed or load was low, and the hydrodynamic effects were then relatively small and the bearing offered less resistance to the misalignment. Sun et al [394] also developed a special test bench for studying the lubrication performance of cylindrical journal bearings considering journal misalignment. The results indicated that the journal misalignment led to the obvious changes at distribution and oil film pressure, oil film thickness and, oil temperature of journal bearing, and the higher the load on the shaft.…”
Section: Simple Journal-bearing Systemsmentioning
confidence: 99%
“…The misalignment caused more significant changes in bearing performance when the rotational speed or load was low, and the hydrodynamic effects were then relatively small and the bearing offered less resistance to the misalignment. Sun et al [394] also developed a special test bench for studying the lubrication performance of cylindrical journal bearings considering journal misalignment. The results indicated that the journal misalignment led to the obvious changes at distribution and oil film pressure, oil film thickness and, oil temperature of journal bearing, and the higher the load on the shaft.…”
Section: Simple Journal-bearing Systemsmentioning
confidence: 99%
“…Sun et al [10] experimentally investigated the behaviour of misaligned journal bearings due to elastic shaft deformation. At a specific amount of rotational load he identified an increase of bearing temperature and a reduction of the maximum hydrodynamic pressure caused by metalmetal contact at the bearing edge.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there are obvious changes in pressure distribution, the maximum pressure, film thickness, the minimum film thickness, and the misalignment moment when misalignment takes place. Later Sun et al [75,76] in 2005 investigated the effects of journal misalignment caused by shaft deformation under static and rotary loads. The results showed that the higher the load on the shaft, the larger is the journal misalignment resulted from shaft deformation, and the more obvious becomes the effect on lubrication performance of journal bearing.…”
Section: Structural Effectsmentioning
confidence: 99%